2013
DOI: 10.1208/s12249-013-9941-5
|View full text |Cite
|
Sign up to set email alerts
|

Solid-State Characterization and Dissolution Properties of Meloxicam–Moringa Coagulant–PVP Ternary Solid Dispersions

Abstract: Abstract. The effect of ternary solid dispersions of poor water-soluble NSAID meloxicam with moringa coagulant (obtained by salt extraction of moringa seeds) and polyvinylpyrrolidone on the in vitro dissolution properties has been investigated. Binary (meloxicam-moringa and meloxicam-polyvinylpyrrolidone (PVP)) and ternary (meloxicam-moringa-PVP) systems were prepared by physical kneading and ball milling and characterized by Fourier transform infrared spectroscopy, differential scanning calorimetry, and X-ray… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
16
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 22 publications
6
16
0
1
Order By: Relevance
“…Broadening of PL‐188 endotherm along with the complete absence of Na 2 CO 3 endotherm is an indicator of intermolecular interactions. Aforesaid findings can be supported with the absence of Na 2 CO 3 peaks in MeSD diffractogram, confirming the ternary interaction of NT, PL‐188 and alkalszer . Besides, single T g observed in MeSD formulation is an indicator of molecular level ternary dispersion of NT.…”
Section: Discussionsupporting
confidence: 60%
“…Broadening of PL‐188 endotherm along with the complete absence of Na 2 CO 3 endotherm is an indicator of intermolecular interactions. Aforesaid findings can be supported with the absence of Na 2 CO 3 peaks in MeSD diffractogram, confirming the ternary interaction of NT, PL‐188 and alkalszer . Besides, single T g observed in MeSD formulation is an indicator of molecular level ternary dispersion of NT.…”
Section: Discussionsupporting
confidence: 60%
“…Binary or ternary solid dispersions have been reported to be more successful since they provide physical stability and prevents recrystallization of drug (4,(6)(7)(8)(9). Use of surfactant with carrier enhances the wettability and solubilization of the drug and also assists in drug release (10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…Cognis Laboratories Serobiol Ogiques group formulated Puricare TM and Purisoft TM, two dynamic ingredients based on natural peptides of MO seeds, which offer protection against pollution effects on hairs and skin (Shah et al, ). The salt extract of seeds has also been used with povidone (polyvinylpyrrolidone) to enhance solubility of the partially soluble Non‐Steroidal Anti‐Inflammatory Drugs (NSAIDS) (Noolkar, Jadhav, Bhende, & Killedar, ). A study conducted by Torondel, Opare, Brandberg, Cobb, and Cairncross () concluded the viability of dried and wet leaf powder as a hand‐washing item and indicated dimensions of inhibition of E. coli similar to a nonmedicated liquid soap because of saponin content.…”
Section: Resultsmentioning
confidence: 99%